Advanced numerical insights into failure analysis and strengthening of monumental masonry churches under seismic actions. (September 2019) - Valente, Marco; Milani, Gabriele
Abstract: The seismic response and strengthening of two complex monumental masonry churches located in Northern Italy have been investigated through an advanced macro-modelling FE-based approach. An extensive documentary research and several field surveys have provided a fundamental preliminary knowledge of the two churches. Detailed three-dimensional FE models with a damage plasticity behavior for masonry have been developed and non-linear dynamic analyses have been performed to simulate the damage distribution in the churches and to identify the most vulnerable macro-elements. The analyses have highlighted the effects of geometrical features and masonry coverings on the seismic behavior of the two churches. The examination of the results in terms of tensile damage contour plots, maximum normalized displacements and energy density dissipated by tensile damage has provided a thorough description of the seismic response of both the whole church and the different macro-elements. In this regard, the procedure utilized could be regarded as a general guideline to follow for a realistic insight into the seismic response and failure analysis of large complex masonry structures without box behavior. From the results obtained, a hypothetical strengthening intervention has been implemented in the numerical models of the two churches according to the Italian Code, in order to quantitatively estimate the vulnerability reduction. A decrease of both tensile damage and displacements has been observed for the critical elements of the two churches in the case of strengthened models. Moreover, the results have shown the importance of the presence of the nave masonry covering to increase the effectiveness of the strengthening intervention, preventing the out-of-plane mechanism of the nave walls. Highlights: Failure analysis of two monumental masonry churches under seismic actions. Identification of the critical macro-elements. Effects of geometrical features and coverings on the seismic response. Effectiveness of a strengthening intervention. Strengthening implementation to reduce vulnerability on the base of the NLDAs results.